A review of the flying fish genus Cypselurus (Beloniformes: Exocoetidae). Part 3. Revision of the subgenus Cypselurus sensu stricto with descriptions of one new species and four new subspecies and reinstatement of Cypselurus crockeri Seale and Exocoetus socotranus Steindachner - Shakhovskoy, Ilia B.; Parin, Nikolay V. (Zootaxa, 2024)
The third and final part of the review of flying fishes of the genus Cypselurus Swainson, focused on subgenus Cypselurus s.str., is presented. The first and the second parts of the review (Shakhovskoy & Parin 2019, 2022) were devoted to the subgenera Zonocypselurus Parin & Bogorodsky and Poecilocypselurus Bruun. The subgenus Zonocypselurus was shown to be invalid and its species were transferred to the subgenus Poecilocypselurus. Thus, the number of subgenera within the genus Cypselurus was reduced to two. In this third part of the review we found that three species of the subgenus Cypselurus s.str. are polytypic: C. opisthopus (Bleeker) (with subspecies C. o. opisthopus and C. o. crockeri Seale), C. naresii (Günther) [with subspecies C. n. naresii, C. n. ordinarius ssp. n., C. n. septentrionalis ssp. n., C. n. albitaenia ssp. n. and C. n. socotranus (Steindachner)] and C. angusticeps Nichols & Breder (with subspecies C. a. angusticeps and C. a. folletti ssp. n.). Two other species, C. hiraii Abe and C. comatus (Mitchill), showed no taxonomically significant variation. A new species, C. persimilis, intermediate in morphology between C. naresii and C. opisthopus, is described. The morphology of all species (except C. nossibe Shakhovskoy & Parin, 2022) and subspecies at different stages of ontogeny is described and maps of their geographic distribution are included. A provisional classification and key for identification of seven valid species and nine subspecies of the subgenus Cypselurus s.str. is provided.